The Importance of Knowing the Types of Capital and Shares in Establishing and Operating a Company - Layla Hasfajira Br Tambunan; Nadiatul Maghfirah; Hadi Rafli Maulana Srg; Nabila Hilmy Khairunnisa Hasibuan; Amanda Putri Fajrin (ISNU Sumatera Utara, 2025)
Understanding the structure and classification of capital and shares is crucial in the establishment and operation of a company, as these two elements form the basis of financial strength, clarity of ownership, and legal accountability. Capital and shares not only provide the financial resources needed for business growth but also serve as instruments of control and governance within a corporate framework. A lack of understanding of these aspects can lead to financial mismanagement, conflicts between shareholders, and limited access to external financing, particularly among small and medium-sized enterprises. This paper presents a structured analysis of capital, encompassing three main categories: authorized capital, issued capital, and paid-up capital. Furthermore, the paper discusses the types of shares, such as common stock and preferred stock, along with the rights and obligations attached to them. Drawing on theoretical concepts and legal regulations, particularly Law Number 40 of 2007 concerning Limited Liability Companies, this study aims to bridge academic understanding and practical application. This research emphasizes the importance of understanding capital and share structures for entrepreneurs, investors, and company managers to achieve financial stability, legal compliance, and long-term business sustainability.